Uganda : Second Review Under the Policy Support Instrument and Request for Waiver of Assessment Criteria: Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Economic growth has recovered, but higher food and fuel prices have sparked a sharp rise in inflation. Monetary policy has been tightened to contain core inflation and effects of the food and fuel price shocks. The government has allowed for scaling up of infrastructure investment spending. The programmed adjustment of fiscal and monetary policies will help put Uganda on a more sustainable medium-term trajectory. Eliminating tax exemptions and incentives will address the revenue gap. The planned oil revenue management framework is encouraging.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet